Perception of optical illusions in ungulates: insights from goats, sheep, guanacos and llamas - Caterina Berardo; Ruben Holland; Alina Schaffer; Alvaro Lopez Caicoya; Katja Liebal; Paola Valsecchi; Federica Amici (Animal Cognition)
Abstract Optical illusions have long been used in behavioural studies to investigate the perceptual mechanisms underlying vision in animals. So far, three studies have focused on ungulates, providing evidence that they may be susceptible to some optical illusions, in a way similar to humans. Here, we used two food-choice tasks to study susceptibility to the Müller-Lyer and Delboeuf illusions in 17 captive individuals belonging to four ungulate species (Lama guanicoe, Lama glama , Ovis aries, Capra hircus). At the group level, there was a significant preference for the longer/larger food over the shorter/smaller one in control trials. Additionally, the whole group significantly preferred the food stick between two inward arrowheads over an identical one between two outward arrowheads in experimental trials of the Müller-Lyer task, and also preferred the food on the smaller circle over an identical one on the larger circle in the experimental trials of the Delboeuf task. Group-level analyses further showed no significant differences across species, although at the individual level we found significant variation in performance. Our findings suggest that, in line with our predictions, ungulates are overall susceptible to the Müller-Lyer and the Delboeuf illusions, and indicate that the perceptual mechanisms underlying size estimation in artiodactyls might be similar to those of other species, including humans.